Media Representation of the Russia-Ukraine War: A Comparative Discourse Analysis of Reuters and TASS - Billah, Md Masum; Biswas, Arnab (South Asian Journal of Social Sciences and Humanities, 2024)
This study has examined the linguistic differences in news reports published by Reuters and TASS on four distinct incidents during the 2022 Russia-Ukraine war. Employing discourse analysis as the methodological approach and discourse theory as the theoretical framework, the study has revealed significant linguistic and rhetorical disparities between the two media outlets, highlighting divergent ideological stances and power dynamics. The study has found that Reuters and TASS have employed distinct linguistic strategies that shape public ideologies and perceptions. TASS has portrayed the war from a Russian perspective, referring to it as a "special military operation" while excluding Ukrainian viewpoints. In contrast, Reuters has depicted the war as a full-scale invasion and emphasized allegations of war crimes while also excluding Russian viewpoints. Discrepancies have also emerged in reporting casualties and territorial control, with TASS and Reuters presenting conflicting figures and narratives. Neither outlet has cross-checked information, undermining their objectivity and contributing to biased reporting. The study underscores how the language used by TASS and Reuters serves to legitimize their respective positions and influence public perception, reflecting broader geopolitical power dynamics. Both media agencies have produced misleading narratives by relying solely on official statements from both nations without independent verification.